OPTIMIZING SPEAKING SKILLS: UNVEILING CHALLENGES AND DESIGNING SOLUTIONS FOR ELEMENTARY SCHOOL TEACHERS - Rifandi Perdana; Yusup Maulana (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The aim of this research is to uncover challenges and design solutions in optimizing the speaking skills of elementary school students. This study employs a qualitative approach with a phenomenological study type, examining the experiences of two elementary school teachers in Bandung City in developing students' speaking skills. Data collection in this research utilizes interview and observation techniques. The results indicate that students still face difficulties in speaking, especially in formal situations such as expressing opinions, storytelling, and even when answering questions from teachers. Students appear rigid, shy, and fearful during speaking activities, lacking the confidence and courage to speak in class. Both language and non-language factors can be developed by teachers to enhance students' speaking skills. Through this research, teachers unanimously agree that teaching speaking skills is crucial in preparing students for life in society.